Діяльність Сидора Голубовича на початковому етапі державотворення Західноукраїнської Народної Республіки (листопад – грудень 1918 р.) - Камінська, Оксана; Kaminska, Oksana (Lviv Politechnic Publishing House, 2019)
У статті проаналізовано діяльність Сидора Голубовича у період листопада-грудня 1918 р. З’ясовано його роль у державотворчому процесі напередодні створення ЗУНР та участь у роботі першого уряду держави. Зокрема значну увагу зосереджено на висвітленні діяльності політика на посаді державного секретаря судівництва. Показано головні здобутки першого Державного секретаріату у львівський та тернопільський період його роботи.

The article deals with activities of Sydir Holubovych in the period of November-December 1918th. Shows his role in the statebuilding process in the run-up to the creation of the West Ukrainian People’s Republic and participation in the work of the first Government of the State. It is indicated that S. Holubovych, while being a member of the Ukrainian National Council (UNRadi) belonged to the composition of its delegation in Lviv, which together with the military engaged in practical training the re-election of power from the Austrian Governor. With' causing that clause after the November uprising S. Holubovych became one of the main leaders of the ZUNR. Considerable attention is focused on covering the activities of the policy on the position of Secretary of the Government in law Kost Levytskyj. Recognized its role in designing the first State laws of the Republic – the interim Constitution, the law on additions UNRadi representatives from the County and city organizations, the law on the temporary organization of the courts and judicial proceedings, the law on administration, the Ordinance on State prosecutors, official oath of judges and judicial orders, etc. Shown the merits of S. Holubovych in the creation of the currentsystem of legal institutions, no leading to a legal vacuum. Analyzed the main achievements of the first State Secretariat in Ternopil during his work. Noted that of the 12 December 1918th. S. Holubovych was the head of the Government and temporarily to the time of the convening of the session of the UNRadi led all its meetings. It is found that the main issues that deal with the Government in this period were: 1) the case of unification of the WEST with the UPR and the mutual exchange of strategic goods (oil, weapon); 2) expansion of the military structure of the Ukrainian Galician Army (creation of aviation division); 3) creating the Department field gendarmerie; 4) food and sanitary and epidemiological issues; 5) establishing trade ties with Hungary, Austria, Czech Republic, etc.
The activity of Sydir Holubovych at the initial stage of the existence of the West Ukrainian people’s republic (november – december 1918)
Keywords: С. Голубович; Українська парламентська репрезентація; Західноукраїнська Народна Республіка; Українська Національна Рада; Державний секретаріат; національно-державне будівництво; S. Holubovych; Ukrainian parliamentary representation; the West Ukrainian people’s Republic; the Ukrainian National Council; State Secretariat; national and State building; 929 (477.8)